Increasing Students' Creativity and Learning Outcomes on Substance Pressure Materials with The Mind Mapping Learning Method - Nurulwati Nurulwati; Putriana Putriana; Nurhayati Nurhayati; Susanna Susanna; Musdar Musdar (Postgraduate, University of Mataram, 2023)
Science is one of the subjects that is still considered difficult for students to understand so students' mastery of concepts in the learning process is still lacking which causes low creativity and student learning outcomes. This study aims to determine the increase in creativity and learning outcomes of students on substance pressure material with the Mind Mapping learning method. This type of research is quantitative and descriptive using the Pre-Experimental method (One Group Pretest-Posttest Design). This research was conducted at MTsN 6 Kuta Baro East Aceh class VIII-3 with a sample of 20 students, sampling using the purposive sampling technique. The instruments used are observation sheets and test questions. The data analysis technique used is the N-gain test for learning outcomes and the percentage for creativity. The results showed that there was an increase in students' creativity and learning outcomes on the material pressure of substances using the Mind Mapping learning method. The increase in creativity of class VIII-3 students in making Mind Maps is included in the category of very good criteria, from 10% to 50%. The improvement of student learning outcomes in class VIII-3 based on the N-gain test is in the medium category, namely 0.7; 0.45; and 0.3